Digital Madrasah Report Card Application for Student Learning Outcomes Assessment - Muhammad Ali Nurdin; Abd. Halim Musthofa (Institut Agama Islam Tribakti Kediri, 2020)
This study aims to describe the Implementation of Digital Madrasah Report Card Application in the assessment of student learning outcomes in Madrasah Ibtidaiyah Negeri (MIN) 2 Kediri City. This research is a qualitative case study approach. Data collection techniques carried out by interview, observation, and documentation of the research object. The results showed the process of implementing a digital report card on madrasas in the assessment of student learning outcomes in MIN 2 Kediri was technically in accordance with the guidelines for using the Digital Report Card Application, but the implementation encountered obstacles so that it had not succeeded in achieving the goal of Madrasah ARD in managing assessment of learning outcomes students quickly, precisely, accurately, effectively and efficiently. [Penelitian ini bertujuan untuk mendeskripsikan Implementasi Aplikasi Rapor Digital Madrasah dalam penilaian hasil belajar siswa di Madrasah Ibtidaiyah Negeri (MIN) 2 Kota Kediri. Penelitian ini merupakan penelitian kualitatif pendekatan studi kasus. Teknik pengumpulan data dilakukan dengan cara wawancara, observasi, dan dokumentasi terhadap objek penelitian. Hasil penelitian menunjukkan proses pelaksanaan aplikasi rapor digital madrasah dalam penilaian hasil belajar siswa di MIN 2 Kota Kediri secara teknis sudah sesuai dengan panduan penggunaan Aplikasi Raport Digital, akan tetapi dalam pelaksannaanya mengalami kendala-kendala sehingga belum berhasil mencapai tujuan ARD Madrasah dalam pengelolaan penilaian hasil belajar siswa secara cepat, tepat, akurat, efektif dan efisien]